Internet usage and personality traits: finding relationship in learning institution - Ahlan, Abdul Rahman; Balogun, Naeem Atanda (Transnational Journal of Science and Technology, 2013)
Purpose – This study aims to investigate the relationship that exists between the personality traits of workers and their internet usage activities. In addition, the study also tries to investigate the workers demography and their internet usage. Design/methodology/approach – The study used questionnaire-based survey to gather responses from both the academic and non-academic staff in order to understand their personality traits and their internet usage. Results and Conclusion – Findings of this study shows significant relationship between personality traits and internet usage, where conscientiousness and openness traits are found to influence internet usage activities of workers. Workers demography is found to relate to their internet usage. Research limitations/implications – Limitation of this study is based on the generalisation of the finding that only involve learning institution. The finding of the study paves a way for other research that will involve other organisation. Practical implications – The findings should assist institution to know the calibre of people to be employed base on their personality traits, as it will help in the usage of internet. Originality/value – The research provides useful information for learning institution based on the type of workers employed, their internet usage and personality trait.